SU-8 processing improvement and simulating studies for a Micromegas detector fabrication. (9th August 2021) - Sampaio, M.F.; Marinho, P.R.B.; Cabruja, E.; Lozano, M.; Lima Júnior, H.P.; de Campos, J.B.
Abstract: This paper reports the manufacturing methodology to produce an electron multiplier, a Micromegas device, integrated onto a micro-pixel readout anode using a Silicon wafer as a holder. It describes the improvement in the processing of the insulating grid material SU-8 and electrical tests with the device. For the latter purpose, simulations with Garfield++ are carried out to predict the detector response for different gas mixtures. The Micromegas detector sandwich proposed in this work presents a series of problems, which we have addressed and discussed within this paper. The temperature control throughout the processing of SU-8 is extremely important, to be able to develop it. When developing the final SU-8 layer, we have used an extra photoresist, which combined with the SU-8, resulted in a much-improved shape of the Micromegas SU-8 hole-grid. Electrical testes are performed in order to verify the signals produced by a 55 Fe radioactive source. A gas gain about 1, 3 × 10 2, using Ar/C2 H6 (75/25) mixture, is achieved for the prototype manufactured.